Three-dimensional bioprinting of mucoadhesive scaffolds for the treatment of oral mucosal lesions; an in vitro study - Maryam Koopaie; Duha Hayder Mohammad Ali Nassar; Mahvash Shokrolahi (3D Printing in Medicine, 2022)
Abstract Background Chronic oral lesions could be a part of some diseases, including mucocutaneous diseases, immunobullous diseases, gastrointestinal diseases, and graft versus host diseases. Systemic steroids are an effective treatment, but they cause unfavorable and even severe systemic side effects. Discontinuation of systemic corticosteroids or other immunosuppressive drugs leads to relapse, confirming the importance of long-term corticosteroid use. The present study aims to fabricate a mucoadhesive scaffold using three-dimensional (3D) bioprinting for sustained drug delivery in oral mucosal lesions to address the clinical need for alternative treatment, especially for those who do not respond to routine therapy. Methods 3D bioprinting method was used for the fabrication of the scaffolds. Scaffolds were fabricated in three layers; adhesive/drug-containing, backing, and middle layers. For evaluation of the release profile of the drug, artificial saliva was used as the release medium. Mucoadhesive scaffolds were analyzed using a scanning electron microscope (SEM) and SEM surface reconstruction. The pH of mucoadhesive scaffolds and swelling efficacy were measured using a pH meter and Enslin dipositive, respectively. A microprocessor force gauge was used for the measurement of tensile strength. For the evaluation of the cytotoxicity, oral keratinocyte cells' survival rate was evaluated by the MTT method. Folding endurance tests were performed using a stable microsystem texture analyzer and analytic probe mini tensile grips. Results All scaffolds had the same drug release trend; An initial rapid explosive release during the first 12 h, followed by a gradual release. The scaffolds showed sustained drug release and continued until the fourth day. The pH of the surface of the scaffolds was 5.3–6.3, and the rate of swelling after 5 h was 28 ± 3.2%. The tensile strength of the scaffolds containing the drug was 7.8 ± 0.12 MPa. The scaffolds were non-irritant to the mucosa, and the folding endurance of the scaffolds was over three hundred times. Conclusion The scaffold fabricated using the 3D bioprinting method could be suitable for treating oral mucosal lesions.